Tensile Strength of Core Build up Material to Glass Fiber Post with Different Surface Treatment - Eman M. Yahya (University of Mosul, College of Dentistry, 2017)
Aims: The purpose of this study was to investigate the effects of different surface treatments on the tensile retentive force of fiber reinforced posts (FRPs) to composite core material buildup. Materials and methods: A total of fifty FRPs were randomly divided into five groups (n = 10), the first group was the untreated control group, second group immersion in 24% hydrogen peroxide; third group immersion in 4% hydrofluoric acid gel; fourth group sandblasting with 50um Al2O3 powder, fifth group surface preparation with an Er:YAG laser under power setting (300m), at 2 Hz and 100 uS) for 10 seconds. A cylindrical polyethylene mold was used to surround the treated posts, and the mold was filled with dual cure composite core material buildup. All samples were light cured for 40 seconds through the top of the mold. After 24 hours of storage in water, the post was then grasped with Jacobs chuck attached to the upper member of testing machine and produced tensile loading. Tensile tests were performed at a cross, head speed of 0.5 mm/minute using a universal testing machine. Data were analyzed by One-Way Analysis of Variance followed by Duncan Multiple Range Test at significant difference (p < 0.05). Results: The post core tensile retentive force achieved following pretreatment with hydrogen peroxide and sandblast (Groups 2 and 4) were comparable to each other, and significantly higher than those of other groups in which the post surface had been treated with hydrofluoric acid gel, control group and laser, respectively. Conclusions: surface pretreatment of FRP has significance effect on the tensile retentive force. Sandblasting and hydrogen peroxide are increasing tensile retentive force of FRPs to composite core material buildup greater than those of hydrofluoric acid gel, control and laser group, respectively.